Factors Affecting Implementation of Green Supply Chain Management In Tech Manora Packing: a Case Study - Reddy, Jagannath; ., Jagadish; N, Charanraj; M.N, Praveen; D. Sai Rohith, Y; Kumar. B, Sathish (International Journal of Engineering and Technology, 2018)
The concept of Green Supply Chain Management (GSCM) is achieving high level implication that can help to reduce the harmful effect of manufacturing activities on the environment. The prime objective is to identify the factors affecting implementation of green supply chain management in Tech Manora packing industry. The collection of data combined primary and secondary sources, the primary source of data isÂ approaching with industry expert by questionnaires. The secondary source of data that is published articles related to GSCM. This study exposed that the most prominent factors affecting implementation of green supply chain management in Tech Manora industry, including lack of knowledge, top management commitment, high cost investment, lack of Government support, lack of information Technology, lack of learning capacity to evaluate GSCM. Finally this study recommends that tech menorah packing industry and its partners should organize joint seminars and workshops to sensitize the staff and suppliers on the benefits of green supply chain management. Further thisÂ study will help to the small scale industries to understand the factors affecting while implementation of GSCM. Â Â